Geofluids : developments in microthermometry, spectroscopy, thermodynamics, and stable isotopes - Hurai, Vratislav; Huraiova, Monika; Slobodnik, Marek; Thomas, Rainer (Vapor-Liquid Equilibrium Data Bibliography, 2015)
Geofluids: Developments in Microthermometry, Spectroscopy, Thermodynamics, and Stable Isotopes is the definitive source on paleofluids and the migration of hydrocarbons in sedimentary basins-ideal for researchers in oil and gas exploration. There's been a rapid development of new non-destructive analytical methods and interdisciplinary research that makes it difficult to find a single source of content on the subject of geofluids. Geoscience researchers commonly use multiple tools to interpret geologic problems, particularly if the problems involve fluid-rock interaction.